The Comparison Of Consumer Decision Making Process For Halal Food In Indonesia : Case Study At Minority And Majority Muslims Area In Indonesia - Isti’anatuz Zumaroh (ACTIVA: Jurnal Ekonomi Syariah, 2019)
A lot of import product come in indonesia, not all of them have halal label. It causes consumers more thoroughly in choosing and deciding to buy the product. Many of issues’s product that is contain pork oil or food that is doubtful of its origin is a major factor in buying a product. Now, in globalization era consume halal labeled products has become a common global trend in society. This research was conducted in Muslim majority and minority areas, that is the provinces of East Java and Bali.The purpose of this study is to compare consumer decision making in buying halal products in Muslim minority and majority areas in Indonesia. This research method used is comparative study. The results of this study indicate that the factors that influence consumer decision making in buying products are halal label, knowledge of the benefits of halal food, religion, awareness of health when consuming halal food in certain areas. The suggestion for halal business entities both factory and grocery / street vendors that produce halal products is better to apply halal label, because it is increasing purchases and attract consumers, especially muslim consumers. And than for the government to be more selective and thorough filter in providing halal label to domestic and imported products. Key Word: halal label, halal product, Indonesia.